Wpływ sztucznej inteligencji na charakterystykę wspólnoty badawczej - Postawa, Andrzej (Studia Edukacyjne, 2025)
Artificial intelligence (AI) is the ability of machines or computer programs to imitate the human way of thinking and acting, to correctly interpret data, to learn, and to use that knowledge to perform specific tasks and achieve goals. Ample studies on artificial intelligence are related to the research community made up of scholars, lecturers, and students. Often, these topics relate to interaction with artificial intelligence or involvement in the educational process. The article examines the relationship between artificial intelligence and the research community. This goal defines the issues and basic research questions: Does the use of AI in academia affect the characteristics of the research community? How does artificial intelligence affect the social nature of this community? Is it related to the psychological image of this community? Does it change the educational process in learning and teaching at the university level, and if so, how? In search of answers to the above questions, it is proposed to analyze the impact of AI on the research community from a multi-disciplinary, sociological, psychological, and pedagogical perspective.